The Brontës and Chekhov in Blake Morrison's We Are Three Sisters (2011). (January 2014) - Brown, Richard; Morrison, Blake
Abstract This is a discussion between Dr Richard Brown of the School of English at the University of Leeds and Professor Blake Morrison, author of the 2011 play We Are Three Sisters which takes the lives of the Brontë sisters as its theme. The discussion took place as part of the interdisciplinary Conference 'Re-Visioning the Brontës' which took place in the University of Leeds on 29 January 2013.